THE PROVISION OF FOOD SUPPLY TO PRESCHOOL EDUCATIONAL INSTITUTIONS IN UZBEKISTAN (BASED ON THE EXAMPLE OF THE 1950 -1970 yy) 1946-1991 (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the provision of food supplies to preschool educational institutions in the collective farm and state farm of the Uzbekistan SSR during the 1950-1970 yy, as well as the operation of milk kitchens. It highlights existing problems related to food quality, food supply, sanitary conditions, and the qualifications of cooks in kindergartens. The establishment and financing of milk kitchens, shortcomings in nutrition, and the effectiveness of health sector control measures are examined. The article also reviews government decisions aimed at improving the food supply of preschool institutions and initiatives for training qualified cooks.